2014
DOI: 10.2337/dc13-2143
|View full text |Cite
|
Sign up to set email alerts
|

The Quality of Periconception Medical Care in Women With Diabetes Needs Improvement

Abstract: OBJECTIVEWe evaluated the quality of periconception medical care in pregnant women with diabetes and assessed the influence of sociodemographic characteristics. RESEARCH DESIGN AND METHODSThe study was based on retrospective data collection from electronic database on cohort of Israeli women at Clalit Health Services (CHS) with pre-existing diabetes who gave birth in 2008-2011. It included data on A1C and other laboratory test results, prescription fillings, diet and ophthalmology consultations, and sociodemog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 29 publications
(37 reference statements)
1
5
0
Order By: Relevance
“…While there are a number of studies examining general preconception care from the practitioner perspective both internationally [26] and within Australia [27], these do not focus on care for women with pre-existing type 2 diabetes or Aboriginal women. Consistent with our findings of low rates of preconception care among Aboriginal women, existing evidence has identified that uptake of preconception care among women with T2DM was less likely in women from minority ethnicities and socioeconomic deprivation [28][29][30].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…While there are a number of studies examining general preconception care from the practitioner perspective both internationally [26] and within Australia [27], these do not focus on care for women with pre-existing type 2 diabetes or Aboriginal women. Consistent with our findings of low rates of preconception care among Aboriginal women, existing evidence has identified that uptake of preconception care among women with T2DM was less likely in women from minority ethnicities and socioeconomic deprivation [28][29][30].…”
Section: Discussionsupporting
confidence: 91%
“…The higher recommended dose of folic acid was prescribed by 40% of practitioners in this study. Other studies assessing preconception folate in women with pre-existing diabetes report 45% of women had folate supplementation of any dose [29,30].…”
Section: Discussionmentioning
confidence: 99%
“…Despite the apparent effect of this process on the outcome of pregnancy of diabetic women, presenting and receiving this care still faces challenges. [ 6 ],[ 7 ],[ 8 ] Given that specific situation of diabetic women, PCC for diabetic women is more complicated than nondiabetic and requires more time, cost, and professional consultation on cardiovascular, renal, retinal and drug use, family planning, etc. [ 1 ] Therefore, diabetic women face more and more challenges than nondiabetics in receiving PCC.…”
Section: Introductionmentioning
confidence: 99%
“…[ 7 ],[ 10 ],[ 11 ] The lack of involvement of spouses in this process, the inadequacy of services provided in health centers, the lack of awareness of these women about the PCC process, and problems related to caring for the other child are among the individual barriers mentioned in various studies. [ 8 ],[ 10 ] Most of these studies are qualitative researches and have noted some of the obstacles in general, while the rank of barriers in terms of importance has not been determined. On the contrary, generalizability is not possible in qualitative studies.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation